(untitled) (Dhaka University Journal of Science, 2021)
Three mixed ligand complexes of copper(II) with adenine and dicarboxylic acids have been synthesized. The resulting complexes were characterized by their melting point, solubility, metal content analysis, FT-IR and UV-visible spectroscopy, magnetic measurement, thermal analysis, cyclic voltammetric measurement and X-ray powder diffraction study. The products are microcrystalline powder, slightly soluble in water and decompose at high temperature. Under experimental condition, the ligands adenine (Ade) behaves as a neutral ligand, whereas oxalic acid (OxH2), succinic acid (SucH2) and tartaric acid (TarH2) are doubly deprotonated to form dianionic ligands that are coordinated to the Cu(II) ion. The Cu(II) content analysis of the complexes confine to their stoichiometry [Cu(Ade)(L)(H2O)] (L = Ox, Suc, or Tar dianion). Electrochemical redox behavior of the complexes in their reaction medium was also examined. They exhibit quasi-reversible one-electron transfer processes. Dhaka Univ. J. Sci. 69(2): 76-81, 2021 (July)